Terapi Pemaafan untuk Menurunkan Tingkat Kecemasan Remaja Korban Kekerasan - Sherli Kurnia Oktaviana (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2022)
The purpose of this study is to examine the effect of forgiveness therapy on decreasing anxiety level of the teenager victim of abuse. The research design used quasi-experimental pretest-posttest control group design. The participants were 22 teenagers aged 15-18 years old that were grouped into experimental and control groups. The instrument used Depression Anxiety Stress Scale by Lovibond and Lovibond (1995) and adapted into Indonesian by Damanik (2014). The data analysis used two independent sample test with Mann Whitney test. The analysis results of pretest and posttest show there is difference of anxiety level between experimental and control groups. The given therapy has a significant effect size of 84.6%.